James Madison : a son of Virginia & a founder of the nation - Broadwater, Jeff (University of North Carolina Press, 2012)
This work chronicles the President's life, including his role in the battle for religious freedom in Virginia, his contributions to the adoption of the Constitution, and his performance as commander in chief during the War of 1812. James Madison is remembered primarily as a systematic political theorist, but this bookish and unassuming man was also a practical politician who strove for balance in an age of revolution. In this biography, the author focuses on Madison's role in the battle for religious freedom in Virginia, his contributions to the adoption of the Constitution and the Bill of Rights, his place in the evolution of the party system, his relationship with Dolley Madison, his performance as a wartime commander in chief, and his views on slavery. In these pages Madison emerges as a remarkably resilient politician, an unlikely wartime leader who survived repeated setbacks in the War of 1812 with his popularity intact. And here the author also shows that despite his keen intelligence, the more Madison thought about the issue of race, the more muddled his thinking became, and his conviction that white prejudices were intractable prevented him from fully grappling with the dilemma of American slavery.